Optical properties of sol-gel materials doped with ethyl 2-(7-hydroxy-2-oxo-2H-chromen-4-yl) acetate - Ahmed, Gyulyay; Petkov, Ivan; Gutzov, Stoyan (European Journal of Chemistry, 2010)
Transparent sol-gel glassy monoliths doped with coumarin molecules [ethyl 2-(7-hydroxy-2-oxo-2H-chromen-4-yl) acetate] displaying a strong blue luminescence are characterized by optical spectroscopy, X-Ray diffraction, SEM and TG/FT-IR spectroscopy. The UV/Vis, luminescence and excitation spectra of the doped sol-gel materials and of ethanol solutions of coumarin are discussed. The coumarin optical spectra are used as a probe for incorporation in the gel structure.